Odpowiedzi

2009-11-25T19:57:29+01:00
1) (x+7)(2x-1)=2x²-x+14x-7 =2x²+13x - 7
2) (2a-1)(a+4)=2a²+8a-a-4=2a²+7a-4
3) (4a-1)(2-3a)=8a-12a²-2+3a=11a-12a²-2
4) (x+√₅)(x-√₅)=x²-x√5+x√5-√25 = x²-5
5) (2y-√₃)(y+1)=2y²+(2y-y√3)-√3
6) (a+√₂)(a-√₃)=a²-a√3 + a√2 -√6
7) (2√₂+k)(√₂-k)= 2√4 + 2k√2 + k√2 - k²=2√4 + 3k√2 - k²
Najlepsza Odpowiedź!
2009-11-25T19:57:53+01:00
1) (x+7)(2x-1)=2x²-x+14x-7=2x²+13x-7
2) (2a-1)(a+4)=2a²+8a-a-4=2a²+7a-4
3) (4a-1)(2-3a)=8a-12a²-2+3a=-11a-12a²-2
4) (x+√₅)(x-√₅)=x²-5
5) (2y-√₃)(y+1)=2y²+2y-√3y-√3
6) (a+√₂)(a-√₃)=a²-a√3+a√2-√6
7) (2√₂+k)(√₂-k)=4-2√2k+k√2-k²=4-√2k-k²
2009-11-25T19:59:14+01:00
1. 2x do kwadratu -7
2.2a do kwadratu -4
3.8a-9a do kwadratu-2
4.x do kwadratu-5
5.2y do kwadratu -pierwiastek z trzech
6.a do kwadratu- pierwiastek z sześciu
7.4-k